(untitled) (Journal of Technology and Operations Management, 2019)
Private healthcare in Malaysia is one of the industries that contributes toward National GDP. However, increasing costs and waste has led to the issue of sustainability. Numerous studies examined the impact of lean healthcare practices on organisational performance. However, there is limited research examining the level of lean healthcare practices among private hospitals. Hence, this study attempted to investigate the level of lean healthcare implementation that lead to enhanced operational performance. The sociotechnical and operational aspects are variables adopted to measure the level of implementation of lean healthcare practices on operational performance. The questionnaire was developed based on previous literature, comprising three aspects, namely operational (24 items), sociotechnical (8 items), and operational performance (10 items). Out of 184 private hospitals in Malaysia, 118 were randomly selected, and 54 questionnaires were returned and used for analysis. Rasch quality control was applied to ensure that the instrument was valid, reliable, and able to measure what it is supposed to measure. It was found that sociotechnical aspect is difficult to implement as compared to operational aspect. Motivation factor dimensions contribute the highest mean value, which is indicative that if an organisation is able to improve this dimension, it is then able to further improve the organisational performance.